Applications of hyperthermic intraperitoneal chemotherapy for metastatic colorectal cancer. Issue 9 (2nd September 2017) - Hornung, Matthias; Werner, Jens M.; Schlitt, Hans J.
ABSTRACT: Introduction : Cytoreductive surgery (CRS) combined with hyperthermic intraperitoneal chemotherapy (HIPEC) plays a pivotal role in the current treatment of peritoneal carcinomatosis (PC) from colorectal cancer (CRC). Since the first demonstration, benefits for patients and especially an increase in survival have been described. In recent years, feasibility, efficacy and safety of HIPEC have been improved and progress has been made in understanding its oncological mechanism. Areas covered : In this article, leading publications have been reviewed including clinical trials to describe the clinical presentation of PC due to CRC and present recent evidence of the CRS/HIPEC procedure. The surgical approach including evaluation of the extent of PC is described and, in addition, the article reports about different HIPEC techniques as well as several protocols. Furthermore, the development and prognostic benefit of the combination of intraperitoneal and intravenous chemotherapy are outlined. Consideration has been given in particular to patient selection and the use of HIPEC if complete cytoreduction is not feasible. Expert commentary : The CRS/HIPEC procedure represents a curative approach to treat patients with PC from CRC. However, surgical skills and the HIPEC technique still require specialized oncological centers.